1969
DOI: 10.1002/pol.1969.150070218
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of acrylonitrile by V5+–lactic acid system in aqueous sulfuric acid

Abstract: Kinetics of polymerization of acrylonitrile by the redox system V5+–lactic acid in sulfuric acid at 20–35°C was studied. Oxidation of lactic acid by V5+ in the absence of monomer was also carried out under identical conditions. The rates of polymerization, V5+ disappearance and the chainlengths of polyacrylonitrile were measured. From the results it is concluded that the polymerization reaction is initiated by an organic free radical arising from the V5+–lactic acid reaction with termination by V5+ ions. Mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

1972
1972
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 5 publications
2
4
1
Order By: Relevance
“…The availability of the acrylamide at the micellar interfaceis an increase in its concentration, and leads to the rate enhancement. The independence of -R V on monomer concentration was also observed in other redox systems [29,30]. 1.985) obtained from bilogarithmic plot of R P(obs) vs. AM ( Figure 2).…”
Section: Effect Of Acrylamide Concentrationsupporting
confidence: 71%
“…The availability of the acrylamide at the micellar interfaceis an increase in its concentration, and leads to the rate enhancement. The independence of -R V on monomer concentration was also observed in other redox systems [29,30]. 1.985) obtained from bilogarithmic plot of R P(obs) vs. AM ( Figure 2).…”
Section: Effect Of Acrylamide Concentrationsupporting
confidence: 71%
“…The k,/kt value at 3OoC is 0.27. The k p h t decreases with increase of temperature; a similar observation was made by Santappa et al7 AE values for k , (26.4 K cal), kp/kt (-7.6 K cal), and As'303 K values for k, (18.34 eu) and k p h t(-86.26 eu) were evaluated.…”
supporting
confidence: 75%
“…The important role of surfactants in polymerization has been studied since the early 1940s. [1][2][3][4] A good amount of work has been done on the polymerization of vinyl monomers in the presence of surfactants with various initiators. Friend and Alexander 5 observed that different cationic surfactants reduced the rate of acrylamide polymerization initiated by potassium persulfate.…”
Section: Introductionmentioning
confidence: 99%
“…They explained it by the assumption that the primary radicals (S 2 O 8 ϭ ) were bound strongly to a positively charged Stern region of the cationic micelles in comparison with the counterion. The permanganate-initiated acrylamide polymerization rate was also reduced in the presence of a cationic surfactant because of the ion-pair binding of MnO 4 Ϫ with a large cation (RN ϩ ), which lowered the rate of formation of primary radicals. 6 Behari and coworkers 7 observed that the anionic surfactant [sodium dodecyl sulfate (SDS)] enhanced the rates, whereas the cationic surfactant [cetyltrimethylammonium bromide (CTAB)] reduced the rates considerably for persulfate-initiated acrylamide polymerization in agreement with the results of Hussain and Gupta.…”
Section: Introductionmentioning
confidence: 99%